Strategic Financial Planning and Business Growth Among Small and Medium Enterprises in North West Nigeria - Bamidele, Vincent Olawale; Dauda, Abdulsalam (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Financial planning is fundamental to the survival and growth of firms, yet in developing regions such as North West Nigeria, its application among small and medium enterprises (SMEs) is often limited due to resource constraints and pervasive uncertainty. Despite SMEs accounting for over half of national employment, the region experiences high SME mortality rates, partly attributed to weak financial management systems.Purpose: This study investigates the impact of strategic financial planning practices on the business growth of SMEs across the seven states of North West Nigeria, providing region-specific empirical evidence.Design/methodology/approach: Anchored on Agency Theory and Pecking Order Theory, the study employs a quantitative correlational design. Primary data were collected from 332 SME owners/managers selected through multistage random sampling. Analytical methods included descriptive statistics, Pearson correlation, Ordinary Least Squares (OLS) regression, and Generalized Linear Modeling (GLM) to ensure robustness.Findings/Result: The results reveal a significant and positive relationship between financial planning and SME business growth (β = 1.846; p